Morphological, Anatomical Study and Geographical Distribution in Iraq of Capparis spinosa L. - A. Zokian, Silva (Iraqi Journal of Science, 2023)
This study dealt with many of morphological, anatomical characteristics and geographical distribution of Capparis spinosa L. that grown wildly in Iraq, The species were compared to the adoption of field and herbarium specimens. A detailed morphological feature of the stem, leaf, fruit and seed were introduced. Anatomical studies reveal constant taxonomic characteristics such as the obvious cuticle on the epidermis of stems and leaves, developed cortex, pith and vascular tissue in stems. From an environmental perspective has been studied the habitat and the distribution of C. spinosa in Iraq that showed inhabit very dry places and had mesophytic and xerophytic habitat.